Investigation of Cancer Cell Migration and Proliferation on Synthetic Extracellular Matrix Peptide Hydrogels - Balion, Zbigniev; Sipailaite, Emilija; Stasyte, Gabija; Vailionyte, Agne; Mazetyte-Godiene, Airina; Seskeviciute, Ieva; Bernotiene, Rasa; Phopase, Jaywant; Jekabsone, Aiste (Frontiers in Bioengineering and Biotechnology, 2020)
Chemical and mechanical properties of tumor microenvironment are essential players in cancer progression, and it is important to precisely control the extracellular conditions while designing cancer in vitro models. The study investigates synthetic hydrogel matrices from polyethylene glycol (PEG) and collagen like peptide (CLP) CG(PKG)4(POG)4(DOG)4 alone and conjugated with either cell adhesion peptide RGD (mimicking fibronectin) or IKVAV (mimicking laminin). Human glioblastoma HROG36, rat C6 glioma cells and A375 human melanoma cells were grown on the hydrogels and monitored for migration, proliferation, projected cell area, cell shape index, size and number distribution of focal contacts in individual cells, and focal adhesion number. PEG-CLP-RGD induced migration of both glioma cell lines, and also stimulated proliferation (assessed as metabolic activity) of HROG36 cells. Migration of C6 cells were also stimulated by PEG-CLP-IKVAV. These responses strongly correlated with the changes in adhesion and morphology parameters of individual cells – projected cell area, cell shape index, and focal contact number. Melanoma A375 cell proliferation was increased by PEG-CLP-RGD, and this was accompanied by decrease in cell shape index. However, neither RGD, nor IKVAV conjugated to PEG-CLP did not stimulate migratory capacity of A375 cells. Taken together, the study presents synthetic peptide hydrogels with ECM-mimicking peptides that allows to explore the effect of extracellular matrix signaling to cancer cells.